Kritik Marcuse terhadap Kultur Konektivitas dan Performatifitas dalam Jaringan (Daring) - Raden Panji Supriyadi; Suharto Suharto; Alexander Seran Bria; Sahrul Ramadhan; Rizky Risdianto (Institut Nalanda, 2026)
This paper examines the contributions of Herbert Marcuse's thought to the development of the Critical Theory tradition, particularly through his analysis of the relationship between technological rationality, consumer culture, and structures of domination in advanced industrial societies. Marcuse demonstrates that technological progress is not neutral, but rather embedded in the logic of power that shapes patterns of social consciousness and behavior. Through the concept of the